2008
DOI: 10.1080/03079450802216611
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the pathogenesis of egg contamination by different serotypes ofSalmonella

Abstract: Salmonella enterica serotype Enteritidis is the predominant serotype associated with egg-borne salmonellosis in humans. Apparently this serotype possesses particular characteristics that increase its chance to contaminate eggs. To identify these characteristics, two Salmonella serotype Enteritidis strains as well as one strain of each of the serotypes Salmonella Typhimurium, Salmonella Heidelberg, Salmonella Virchow and Salmonella Hadar strain were used to examine different aspects related to egg contamination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
1
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 35 publications
4
75
1
6
Order By: Relevance
“…Eles assumiram posição média na imunogenicidade e no efeito em desempenho das aves inoculadas. Estes dados estão de acordo com o trabalho comparativo de Gantois et al (2008) que indicaram maior capacidade de colonização dos órgãos reprodutores da SE e ST em relação a outros sorovares estudados. Aparentemente alguns sorovares possuem características particulares que aumentam a chance de infectar as aves causando perdas zootécnicas levando a um maior estímulo do sistema imune da ave. Conclui-se que existe uma relação entre a intensidade de estímulo do sistema imunológico e o gasto energético dos animais, sendo que microrganismos mais patogênicos repercutem em menor ganho de peso das aves em função do custo para a formação da defesa linfocitária de mucosa.…”
Section: Discussionunclassified
“…Eles assumiram posição média na imunogenicidade e no efeito em desempenho das aves inoculadas. Estes dados estão de acordo com o trabalho comparativo de Gantois et al (2008) que indicaram maior capacidade de colonização dos órgãos reprodutores da SE e ST em relação a outros sorovares estudados. Aparentemente alguns sorovares possuem características particulares que aumentam a chance de infectar as aves causando perdas zootécnicas levando a um maior estímulo do sistema imune da ave. Conclui-se que existe uma relação entre a intensidade de estímulo do sistema imunológico e o gasto energético dos animais, sendo que microrganismos mais patogênicos repercutem em menor ganho de peso das aves em função do custo para a formação da defesa linfocitária de mucosa.…”
Section: Discussionunclassified
“…Studies have shown that some S. Enteritidis phage types (PTs) are more invasive than others (Hinton et al, 1990;Roy et al, 2001), but other similarly designed studies could not identify any difference in the invasiveness or colonisation ability between different phage types (Barrow, 1991). Despite its peculiar affinity for the reproductive tract of hens, S. Enteritidis is not the only serotype able to colonise ovaries and oviducts and contaminate forming eggs (Keller et al, 1997;Okamura et al, 2001a;Gast et al, 2004;Gantois et al, 2008).…”
Section: Factors Influencing Salmonella Pathogenesis In Chickensmentioning
confidence: 99%
“…Enteritidis is particularly successful in invading the hen reproductive tract and contaminating eggs (Humphrey, 1994;Okamura et al, 2001a;Okamura et al, 2001b;Gast et al, 2004;Gantois et al, 2008). The success of S. Enteritidis in the transovarian transmission route can be associated with the presence in this serovar of the SEF14 fimbriae (which might be involved in the colonization of the reproductive organs), the presence of the yafD gene (which is essential for resistance in the albumen), and with the lipopolysaccharide structure, a key factor in oviduct persistence and survival in egg albumen (Lu et al, 2003;Coward et al, 2013), particularly at a hen body temperature of 41.5 °C (Coward et al, 2013).…”
Section: Primary Contaminationmentioning
confidence: 99%
See 2 more Smart Citations